β-Mannanase production by aspergillus flavus in solid-state fermentation of palm kernel cake - Wong, Y. P.; Saw, Horng Yuan; Jidon Janaun; K. Krishnaiah; A. Prabhakar (Springer, Boston, MA, 2013)
β-Mannanase production in batch solid-state fermentation (SSF) of palm kernel cake (PKC) was evaluated with flasks and a laterally aerated moving bed (LAMB) bioreactor using Aspergillus flavus UMS01. Optimum condition for flask SSF was 110 % moisture content, initial pH 6, 30 °C and particle size 855 μm, yielding 383 U g−1 dry PKC after 120 h. Under the same condition and particle size <5 mm, SSF in LAMB produced 276 U g−1 dry PKC at an optimal gas flow of 4.4 m s−1 in just 96 h. Optimal β-mannanase production was consistent with highest fungal growth and mannose production; to support increasing fungal growth, secretion of β-mannanase increased to degrade mannans in PKC, producing mannose for microbial consumption. A. flavus UMS01 showed promising attributes as a β-mannanase producer via SSF of PKC in flasks and LAMB bioreactor.